Republic of Armenia : Second Review Under the Stand-By Arrangement, Request for Waiver of Nonobservance of Performance Criterion, Modification of Performance Criteria, and Rephasing of Purchases; Staff Report; Press Release on the Executive Board Discussion; and Statement by the Executive Director and Advisor for the Republic of Armenia. (IMF Staff Country Reports; Country Report ;, 2009)
This paper discusses key findings of the Second Review Under the Stand-By Arrangement (SBA) for Armenia. The authorities met all quantitative performance criteria for end-June and end-September, with the exception of the end-September fiscal balance. All structural benchmarks for end-June and end-September were also implemented. The authorities request a waiver of nonobservance for the end-September fiscal balance performance criterion given the minor and temporary nature of the deviation. IMF staff supports this request, as well as the authorities' request for completing this review.